Persepsi Peranan dan Tanggug Jawab Abdi Dalem Keraton Kacirebonan dalam Pelestarian Warisan Budaya - Warliati, Annisaa Eka (Program Studi S1 Pariwisata, Universitas Muhammadiyah Gorontalo, 2023)
The Kacirebonan Palace is the youngest palace in Cirebon City, which was founded in 1800. The location of the Kacirebonan Palace at the Cirebon City area, precisely on Jl. Pulasaren. The strategic location makes this palace a tourist attraction, including cultural tourism. In the government of a palace, some courtiers assist a sultan, including in the Kacirebonan Palace. This research is descriptive qualitative research that describes the roles and responsibilities of the courtier at the Kacirebonan Palace. The stages of research were carried out in stages, through interview techniques, documentation, and literature review. The sample of this research were ten courtiers at the Kacirebonan Palace who had roles and responsibilities wholeheartedly for the creation of a harmonious government at the Kacirebonan Palace and full of a sense of responsibility for the mandate given by the Sultan of the Kacirebonan Palace. The results of this study explained that every courtier has a role and responsibility to preserve cultural heritage, both tangible and intangible.